Juridical Analysis of Legal Certainty in the Resolution of Land Rights Disputes in Makassar City - Zaqia Rezky Intan Saputri; Muhammad Kamal; Askari Razak (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study analyzes legal certainty in the resolution of land rights disputes in Makassar City and identifies factors affecting the effectiveness of non-litigation dispute settlement. Land disputes remain a significant legal issue in Indonesia, particularly in rapidly developing urban areas. This research applies a combined normative and empirical legal approach with qualitative analysis. Normative research examines legal norms and regulations governing land dispute resolution, while empirical research explores their implementation in practice. Data were collected through literature review, interviews, and field observations involving judges, officials of the National Land Agency (BPN), and legal practitioners in Makassar. The findings indicate that although mediation and other non-litigation mechanisms offer faster and less costly solutions, their implementation remains suboptimal. The effectiveness of legal certainty is influenced by several factors, including community culture, legal knowledge, legal structure, legal awareness, and supporting facilities and infrastructure. Among these, facilities and infrastructure as well as community culture are the most dominant factors. Strengthening institutional capacity, improving mediator competence, and enhancing legal literacy are essential to improve non-litigation land dispute resolution in Makassar City